OPTIMIZING THE TAX BURDEN OF COMPANIES IN THE CONTEXT OF GLOBAL CHANGES: NEW STRATEGIES AND RISKS - Mirkamol Sagdiev (American Journals, 2025)
This article examines current trends in corporate taxation driven by globalization, digitalization, and geopolitical instability. New strategies for optimizing companies' tax burdens, as well as the associated risks, are analyzed. Emphasis is placed on legal approaches to tax planning, the transformation of tax functions, and the importance of tax risk management in a rapidly changing world.
Keywords: Tax optimization, corporate taxes, transfer pricing, international planning, tax risks, globalization, digitalization, ESG, Pillar Two, financial planning.